Improving Energy Adaptivity of Constructive Interference-Based Flooding for WSN-AF - Dapeng Cheng; Yanyan Mao; Yin Wang; Xiangrong Wang (International Journal of Distributed Sensor Networks)
Constructive interference (CI) is a synchronous transmission technique for multiple senders transmitting the same packet simultaneously in wireless sensor networks (WSNs). CI enables fast and reliable network flooding in order to reduce the scheduling overhead of MAC protocols, to achieve accurate time synchronization, to improve link quality of lossy links, and to realize efficient data collection. By achieving microsecond level time synchronization, Glossy realizes millisecond level CI-based flooding and 99% reliability. However, Glossy produces substantial unnecessary data forwarding, which significantly reduces the network lifetime. This is a very critical problem, especially in energy-limited large-scale wireless sensor networks for agriculture and forestry (WSN-AF) system. In this paper, we present an energy adaptive CI-based flooding protocol (EACIF) by exploiting CI in WSN-AF. EACIF proposes a distributed active nodes selection algorithm (ANSA) to reduce redundant transmissions, thereby significantly reducing energy consumption and flooding latency. We estimate the performance of EACIF both with real data traces and with uniformly distributed topology. Simulation results show that EACIF achieves almost the same packet reception ratio (PRR) as Glossy (e.g., 99%), while reducing 63.96% energy consumption. EACIF also reduces 25% flooding latency. When the packet interval is 30 seconds, EACIF achieves 0.11% duty cycle.